PENGARUH KEBERADAAN KOMITE MANAJEMEN RISIKO (RMC) DAN KARAKTERISTIKNYA TERHADAP KINERJA LINGKUNGAN PERUSAHAAN - Daffa Faqih Saputra; Agung Juliarto (Diponegoro Journal of Accounting, 2023)
This research is a quantitative study aimed at analyzing the influence of the presence of risk management committees (RMC) and their characteristics, namely structure and individual capacity of RMC, on corporate environmental performance. Corporate environmental performance in this study is measured by Environmental, Social, and Governance (ESG) scores.The sample in this research consists of non-financial companies listed on the Indonesia Stock Exchange from 2017 to 2021, with a total sample size of 325 observations and a sub-sample of 87 observations. The sample selection was based on purposive sampling method, and multiple linear regression analysis was used as the main method of analysis to test the hypotheses.The results of this research indicate that the presence of RMC has a positive and significant effect on corporate environmental performance. However, having a separate RMC structure from other committees did not prove to be more effective in improving corporate environmental performance. As for specific individual capacity, it does not have a significant influence on corporate environmental performance. On the other hand, generic individual capacity has a positive and significant influence on corporate environmental performance.